The deficiency of chymase mast cell protease 4 exacerbates dextran sulfate sodium salt-induced colitis in mice and is associated with altered microbiota and metabolome profiles - Zhiqiang Li; Zhiqiang Li; Zhiqiang Li; Xiaoyuan Kuang; Dashuang Mo; Magnus Åbrink; Ge Shan; Jin-ping Li; Can Yang; Yuexi Wang; Tao Shen; Weiwei Yu (Frontiers in Cellular and Infection Microbiology)
IntroductionUlcerative colitis (UC) is a chronic gastrointestinal disease characterized by symptoms of abdominal pain and diarrhea. Chymase is a serine protease released by the mast cells and is highly expressed in patients with UC. However, its role in disease pathogenesis remains poorly understood. In mice, mast cell protease-4 (MCP-4) is considered as the functional homolog of human chymase, sharing similar enzymatic activity and biological roles.MethodsTo investigate the role of MCP-4 in UC, we induced colitis in Mcpt-4-deficient (Mcpt-4∆Cre) and littermate control (Mcpt-4fl/fl) mice using 2% dextran sulfate sodium salt (DSS) for 8 days followed by 2 days of water. After sacrifice, colon length was measured, and tissue samples were analyzed by histology (H&E and toluidine blue staining), qPCR, and protein assays. Colonic contents were collected for microbiota and metabolomics analysis.ResultsThe results show that the Mcpt-4-deficiency exacerbated colitis, as reflected by the significantly greater weight loss, higher histological scores, elevated levels of myeloperoxidase and most of determined cytokines. Furthermore, the Mcpt-4∆Cre colitis mice displayed a distinct shift in colonic microbiota composition, notably with significantly increased abundance of bacteria (Akkermansia and Turicibacter), associated with potentially worsened inflammation in colitis models. In addition, metabolomic profiling revealed alterations in colonic metabolites involved in key Kyoto Encyclopedia of Genes and Genomes (KEGG) pathways, including NF-kappa B signaling, Th1 and Th2 cell differentiation.DiscussionThese findings reveal that the mouse chymase MCPT-4 plays important roles in maintaining the intestinal homeostasis during colitis, potentially through regulation of colonic cytokines, microbial and metabolic networks.